The Influence of National Unification on the Interpretation of Suicide Statistics in Nineteenth-Century Germany and Italy - Maria Teresa Brancaccio; David Lederer (Criminocorpus)
Wagner’s and Morselli’s contributions, whenever they are recognized, are generally considered in relation to transnational debate on suicide or nineteenth century statistical methods, or their influence on Emile Durkheim’s Suicide (1897). Here, our aim is to highlight Wagner’s and Morselli’s contributions in relation to the process of national unification underway in both Germany and Italy.